The Effectiveness of Digital Flashcards in Improving Vocabulary Mastery of Seventh Grade Students of SMP Taruna Sakti Pekanbaru - Selvia, Selvia; Daud, Afrianto; Azhar, Fadly (CV. Rayyan Dwi Bharata, 2026)
This study aims to investigate the effectiveness of digital flashcards in improving the vocabulary mastery of seventh-grade students of SMP Taruna Sakti Pekanbaru as measured through a vocabulary test. The study applied a pre-experimental design involving one group without a control group, in which measurements were conducted before and after the treatment. The data were obtained from a vocabulary test consisting of 30 multiple-choice items given as a Pre-Test and Post-Test. The mean score of the Pre-Test was 64, while the Post-Test mean increased to 86.23, indicating a notable improvement in students’ vocabulary achievement. The results were analyzed using the Wilcoxon Signed-Rank Test, which produced an Asymp. Sig. (2-tailed) value of 0.000. This indicates that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Consequently, it can be concluded that the use of digital flashcards has a positive and significant effect on students’ vocabulary mastery.